Study of various congenital anomalies in fetal and neonatal autopsy - Naik, V. Siva Sankara; Babu, P. Venkata Ramana; Reddy, E. Sudhakar; Prasad, B. V. Sai; Radha, B. Anu; Myreddy, Neeraja; Suman, T. C.; Bharathi, T. (International Journal of Research in Medical Sciences, 2017)
Background: The study of dead is to save the livings. The growing awareness that still births and infant mortalities are unable to reduction has led to a wide spread desire for more information regarding the cause of these deaths. Congenital malformations have become important cause of fetal and neonatal (perinatal) mortality in developed countries and would very soon be increasingly important determinants of fetal and neonatal mortality in developing countries like India. In spite of antenatal diagnostic modality still the fetal autopsy plays the vital role in the conformation as well as identification of congenital anomalies and also for the counseling of the parents, to prevent the fetal congenital anomalies in further pregnancies. This study was undertaken with the purpose of finding out cause of death during the perinatal period at government maternity hospital and pediatric department S.V.R.R.G.G.H. & S.V. medical college Tirupati, and to study the clinical and pathological findings (Gross & microscopic) in fetal and neonatal death. Methods: The present study of congenital anomalies in fetal and neonatal deaths was done at S.V. medical college, Tirupati, over a time period of 2 years from September 2008 to 2010 August. Consent for autopsy in requested compassionately, respectfully and fully informed. The present study included dead fetus and neonates with gestational age above 20 weeks of intra uterine life and within 7 days of post natal life. All fetuses of gestational age <20 weeks and all neonates above 7 days of age were excluded from the study. The study also obtained clearance from the ethical committee of the institution. Autopsy was performed by standard technique adopted by Edith L. Potter. External and internal findings followed by histopathological examination, and autopsy findings were compared with available ultrasound findings. Results: A total of 46 Autopsies performed, 40 (87%) were fetal deaths, 6 (13%) were early neonatal deaths. In a total of 46 fetuses, there were 13 male and 33 female babies. On external examination of 46 fetal and Neonatal (perinatal) deaths, 8 (17.39%) babies showed congenital malformation. On internal examination of the 46 fetal and Neonatal (perinatal) deaths, 4 babies showed internal congenital anomalies. A total of 46 anatomical and histopathologic examinations were done among fetal and neonatal (perinatal) deaths. Out of 13 autopsies on male babies, 2 had congenital malformation and 33 autopsies on female babies, 7 had congenital malformations. Congenital anomalies were commonest in the birth weight group of 1000-1500 grams accounting for 9 cases. Malformations of central nervous system (33.33%) were most common followed by musculoskeletal system (16.66%), genitourinary and respiratory system (8.33%) respectively. Conclusion: Most number of perinatal deaths occurred in low birth weight and preterm babies. Study of malformations greatly helpful in genetic counseling and prenatal diagnosis in successive pregnancies.